Assessing Soil Erosion by Agricultural and Forestry Production and Proposing Solutions to Mitigate: A Case Study in Son La Province, Vietnam - X. H. Nguyen; A. H. Pham (Applied and Environmental Soil Science)
Son La is a province in the Northwest region of Vietnam; this province has diverse terrains with elevation ranging from 100 m to 2,900 m. Due to lack of cultivating lands, farmers still cultivate lands with steep slope, even above 25o. Consequently, the soil erosion has occurred hugely and the time for productive cultivation has been shortened. Therefore, it is necessary to assess the actual soil erosion, analyzing causes and proposing solutions to mitigate soil loss in the Son La province. Application of GIS technology and the Universal Soil Loss Equation (USLE) to predict soil erosion showed that the soil eroded at a very low level (0–1 ton·ha−1·year−1) accounted for the largest proportion with 56.49% of the area. Low level (1–5 ton·ha−1·year−1), medium level (5–10 ton·ha−1·year−1), and high level (10–50 ton·ha−1·year−1) eroded areas account for 8.52%, 7.88%, and 1.41%, respectively, of the area. Soil is eroded in very high level (>50 ton·ha−1·year−1), accounting for 25.7% of the study area. Research on solutions to mitigate soil erosion in Mai Son district showed that, for the cultivation of perennial crops (coffee), when planting on following contour lines, the amount of soil lost annually due to erosion is 63.37 ton·ha−1, while the cultivation following level top bench terrace soil loss is 39.55 ton·ha−1. If more grass strips were planted, the amount of soil lost annually due to erosion was reduced by 71% compared to traditional solutions. For this solution, when intercropping soybean, the soil erosion was reduced by 63–76% compared to the traditional methods. For cultivation of annual crops (maize) where the traditional methods of cultivation, namely, burning, ploughing, and seeding, are followed, the average loss of soil annually is 64.06 ton·ha−1. This value was 45.04 ton·ha−1 and 41.96 ton·ha−1, respectively, as the minimum soil tillage measure and no-tillage measure were used. When using the stems of maize after harvesting to cover lands following contour lines and terraces, soil erosion decreased by 38–59% compared to traditional solutions, while intercropping with legumes, soil loss due to erosion decreased 50–68% compared to traditional measures.